A socio-economic analysis of biomethane in the transport sector: The case of Italy. (15th July 2019) - D'Adamo, Idiano; Falcone, Pasquale Marcello; Ferella, Francesco
Highlights: Green gas is a sustainable alternative than natural gas. The biomethane supports the development of circular economy models. Multiple case-studies are analysed for the Italian context. The increase of renewables in transport sector favors the decarbonisation of energy systems. The role of subsidies is crucial for the development of the sector. Abstract: The transport sector has a low penetration of renewable energy, and this presents a serious obstacle to tackling climate change. Biomethane is seen as a decarbonisation solution, but only some European countries have pursued its development. Italy is one of these countries, having released a decree to stimulate development of the sector. The present work considers two typologies of substrate (the organic fraction of municipal solid waste and by-products) used in three sizes of plants (125 m 3 /h, 250 m 3 /h and 500 m 3 /h). A detailed socio-economic analysis is presented and policy implications are provided. The recovery of waste enables the creation of a circular economy, but the economic feasibility of such a model is verified in only some scenarios. A sensitivity analysis on the critical variables is conducted to support investment in this area. The use of green gas is found to be capable of significantly reducing greenhouse gas emissions in the transport sector, but the economic value of any environmental externality is low due to the value of carbon dioxide.